A Case study on Enterprise Collaboration and Interoperability in the Cloud (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
Increasingly, current software enables large and small companies to interact via cloud computing. Services offered in the cloud facilitate collaboration between databases and are a part of the information infrastructure that allows companies and organisations to move or integrate data within the cloud. This paper presents an analysis of the use of open source services that support cloud-based enterprise collaboration and interoperability. A practical case of an application of enterprise collaboration in the field of product development and production planning in the Slovenian automotive sector is presented. The results of solutions enable small and medium-sized companies, which have limited financial assets, to purchase one of the legacy systems and to become integrated within the supply chain of the automotive cluster of Slovenia. At the same time, the paper strives to establish the difference, if any, between conventional collaboration among companies and enterprise collaboration and interoperability in the cloud.